Lipoprotein Ratios as Biomarkers for Assessing Chronic Atherosclerosis Progression: Rasio Lipoprotein sebagai Biomarker untuk Menilai Perkembangan Aterosklerosis Kronis - Abbas Mohsin Abbas; Iman H Shewael; Osama A. Mohsein (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Lipoprotein ratios are critical biomarkers for assessing chronic atherosclerosis progression, providing insights into lipid metabolism imbalances and cardiovascular risk. Specific Background: While their role in cardiovascular disease is established, their correlation with inflammatory markers in chronic atherosclerosis remains underexplored. Knowledge Gap: Limited studies have comprehensively examined the interplay between lipid dysregulation and systemic inflammation in chronic atherosclerosis. Aims: This study evaluates the significance of lipoprotein ratios as biomarkers for chronic atherosclerosis progression and their association with inflammatory markers. Methods: A case-control study at Al-Habbobi Teaching Hospital (October 1, 2024 – February 1, 2025) included 60 chronic atherosclerosis patients and 30 healthy controls. Lipoprotein ratios (LDL/HDL, TC/HDL, non-HDL cholesterol) and inflammatory markers (CRP, IL-6, IFN-γ, adiponectin, MCP-1) were analyzed using ELISA, with atherosclerosis severity assessed via intima-media thickness (IMT). Results: Patients exhibited significantly elevated BMI, smoking prevalence, hypertension, lipoprotein ratios (p < 0.001), and inflammatory markers, indicating chronic inflammation. Lipid dysregulation strongly correlated with inflammation. Novelty: This study provides novel evidence linking lipoprotein ratios with inflammatory responses, reinforcing their role as integrated biomarkers. Implications: Understanding lipid-immune interactions may improve early diagnosis, risk stratification, and targeted therapy development for chronic atherosclerosis. Highlights: Lipoprotein ratios and inflammation contribute to chronic atherosclerosis progression. Case-control study analyzing lipoprotein ratios, inflammatory markers, and IMT. Strong correlation between lipid dysregulation, inflammation, and atherosclerosis severity. Keyword: Lipoprotein Ratios, Chronic Atherosclerosis, Inflammatory Markers, LDL/HDL, Immune Response, Cardiovascular Risk